Examining the influence of mathematical anxiety on the global perspective of junior high school students - Nurhayati; Resy Nirawati; Nindy Citroresmi Prihatiningtyas; Nurul Husna; Rika Wahyuni; Mariyam; Elisabet Novita; Erros Chandra; Adenia Wirasati (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Mathematics is frequently perceived by students as a challenging subject, which can lead to mathematical anxiety. Such anxiety may influence students’ learning experiences and their ability to interpret broader global issues. Aims: This study aims to examine the influence of mathematical anxiety on the global perspective of junior high school students. Method: A quantitative correlational design was employed involving 33 eighth-grade students from a public junior high school in Pontianak, Indonesia. Data were collected through a mathematical anxiety questionnaire and a global perspective questionnaire. Mathematical anxiety was examined through psychological, physiological, and social components. Prior to the main analysis, prerequisite tests including normality, linearity, and homoscedasticity were conducted. The relationship between variables was then analyzed using simple linear regression. Results: The analysis indicates that mathematical anxiety contributed 10.3% to students’ global perspective (R² = 0.103). However, the regression results show that mathematical anxiety did not have a statistically significant influence on students’ global perspective (p = 0.069 > 0.05). This finding suggests that students’ understanding of global issues may be shaped by other educational or social factors beyond mathematics-related anxiety. Conclusion: Although mathematical anxiety was not found to significantly affect students’ global perspective, addressing anxiety in mathematics learning remains important. Creating supportive learning environments and contextual learning experiences may help students engage more confidently with mathematics.